POSEY’S ALTRUISM AND HER HIGH EMPATHETIC DEEDS IN MITCH ALBOM’S NOVEL FOR ONE MORE DAY - Riska Dewi Ramadhani; Happy Julia Rahmadianti; Novanda Lukwita Hakim; Rommel Utungga Pasopati; Rindrah Kartiningsih; Dimas Eko Saputro (LPPM Universitas PGRI Adi Buana, 2025)
This paper examines the relationship between altruism and high empathetic deeds through the character Posey in Mitch Albom’s For One More Day. Altruism, as a selfless concern for the welfare of others based on a genuine desire to help them, is directly related to the capacity for empathy—especially when one does so without expecting anything in return. Using qualitative literary analysis, this study focuses on Posey’s emotional sensitivity and selfless actions toward her son, Charley Benetto, and those around her. Drawing on theories of empathy and altruism, this study explores key scenes that demonstrate Posey’s ability to understand and respond to the emotional needs of others with compassion. The study’s findings suggest that Posey’s altruism is rooted in her high empathy, which manifests in her caring, nurturing, and emotional support. In conclusion, Posey’s character demonstrates how empathy is a driving force behind altruistic behavior in literature and in human life.